Spectral effects on symbiodinium photobiology studied with a programmable light engine - Wangpraseurt, Daniel (2014)
The spectral light field of Symbiodinium within the tissue of the coral animal host can deviate strongly from the ambient light field on a coral reef and that of artificial light sources used in lab studies on coral photobiology. Here, we used a novel approach involving light microsensor measurements and a programmable light engine to reconstruct the spectral light field that Symbiodinium is exposed to inside the coral host and the light field of a conventional halogen lamp in a comparative study of Symbiodinium photobiology. We found that extracellular gross photosynthetic O2 evolution was unchanged under different spectral illumination, while the more red-weighted halogen lamp spectrum decreased PSII electron transport rates and there was a trend towards increased light-enhanced dark respiration rates under excess irradiance. The approach provided here allows for reconstructing and comparing intra-tissue coral light fields and other complex spectral compositions of incident irradiance. This novel combination of sensor technologies provides a framework to studying the influence of macro- and microscale optics on Symbiodinium photobiology with unprecedented spectral resolution.